HUBUNGAN KARAKTERISTIK, INTERAKSI SOSIAL TERHADAP KUALITAS HIDUP LANSIA DI KELURAHAN AEK NAULI PEMATANGSIANTAR TAHUN 2022 - Endang Susilawati; Lidya Feronika Hutabarat (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
Background: In general, the number of elderly is increasing, along with that in elderly, there has been a decline in both physical and mental health. This results in a decrease in the quality of life in the elderly. However, it is hoped that even though they are elderly, the quality of life is maintained and productive. However, there are still elderly people who have less social social interaction. Objectives: To determine the correlation, characteristics, social interaction on the quality of elderly life in Aek Nauli Village, Pematangsiantar in 2022. Methods: This type of research was quantitative analytical with a cross sectional design. The population was all elderly in Aek Nauli Village, about 455 people with 44 people as samples taken. The sampling technique was Systematic Random Sampling. Data was collected using a questionnaire. Results: The results showed 45.5% of the elderly with married status, there was correlation between marital status and the quality of elderly life with p value = 0.01. There was no correlation between gender, age, religion and education with the quality of life of the elderly. As many as (70.5%) elderly have good social interaction and (68.2%) elderly have good quality of life. It was found correlation between social interaction with the quality of elderly life, the results of the Chi Square test with p-value = 0.000. Research suggests the elderly to increase social interaction with family and the environment because they can maintain their quality of life, by diligently participating in Posyandu activities for the elderly.